Probing the bright radio flare and afterglow of GRB 130427A with the arcminute microkelvin imager - Anderson, Gemma; Van der horst, A.; Staley, T.; Fender, R.; Wijers, R.; Scaife, A.; Rumsey, C.; Titterington, D.; Rowlinson, A.; Saunders, R. (Oxford University Press, 2014)
We present one of the best sampled early-time light curves of a gamma-ray burst (GRB) at radio wavelengths. Using the Arcminute Mircrokelvin Imager (AMI), we observed GRB 130427A at the central frequency of 15.7 GHz between 0.36 and 59.32 d post-burst. These results yield one of the earliest radio detections of a GRB and demonstrate a clear rise in flux less than one day after the ?-ray trigger followed by a rapid decline. This early-time radio emission probably originates in the GRB reverse shock so our AMI light curve reveals the first ever confirmed detection of a reverse shock peak in the radio domain. At later times (about 3.2 d post-burst), the rate of decline decreases, indicating that the forward shock component has begun to dominate the light curve. Comparisons of the AMI light curve with modelling conducted by Perley et al. show that the most likely explanation of the early-time 15.7 GHz peak is caused by the self-absorption turn-over frequency, rather than the peak frequency, of the reverse shock moving through the observing bands. © 2014 The Authors Published by Oxford University Press on behalf of the Royal Astronomical Society.